You can only add or subtract like terms. So, you subtract 9x from 2x, which gives you -7x. Then subtract -9 from 3 to get -6. And you are left with -7x -6.
Chat with our AI personalities
2x + 3 = x + 1 Subtract x from both sides: x + 3 = 1 Subtract 3 from both sides: x = -2
4x + 2 = 2x + 5 Subtract through by 2x 2x + 2 = 5 Subtract through by 2 2x = 3 Divide through by 2 x = 1.5 ■
4x-39 = 2x+3, 4x-2x = 42 x=21
You first must use SADMEP or PEMDAS backwards. (parentheses, exponent, multiply and divide, add and subtract) With this information you must ether add or subtract first 2x + 3 = 9 (Now, subtract 3 from each side of the equation) 2x + 3 - 3 = 9 - 3 (and the result is...)2x = 6 (whatever you do to one side of the equation you must do to the other.) 2x = 6 (Divide both sides by 2)2x/2 = 6/2 (and you get...) x = 3
The multiplicative inverse of 3+2x is 1/(3+2x).